PCB (Printed Circuit Board) Etching Machine Using ESP32-Camera Based Internet of Things - Adi Prasetyo; Jamaaluddin Jamaaluddin; Izza Anshory (Universitas Ahmad Dahlan, 2023)
The most important factor in the PCB etching process is timeliness and minimizing work on users. Because in general, the PCB etching process itself is still done manually and there is no timeliness and good results. So, the PCB etching machine tool using Internet of Things based Esp32-Cam is made for users in the PCB etching process. Users can monitor the etching process of the internet of things system using telegram. In the telegram there is a choice of time to carry out the etching process. The components used in this tool power supply as a power source in this tool uses a voltage of 5vdc, Esp32-Cam as a microcontroller, camera features on Esp32-Cam as a photo sender after the etching process time has been completed, RTC (Real Time Clock) as a timer for the PCB etching process, servo motor as a box drive containing water and PCB when the etching process time is selected. The conclusion of the results of this tool is that the device or tool works well and can help users on the PCB etching process efficiently, it's just that there are few challenges for the signal network due to delays in bad internet signals.